Prediction and modeling of connectivity probability in vehicular Ad Hoc networks - Huimin WANG; Haitao ZHAO (Dianxin kexue)
Recently，with the rapid development of vehicular communication technology，IoV（internet of vehicles）as one of the applications of IoT（internet of things），is attracting more and more attention as well as its basic applications.The algorithm of predicting the connectivity probability based on highway model was proposed.Also，the joint distribution of vehicles on highway was studied，and the equation calculating the boundaries of connectivity probability on one road segment was analyzed quantitatively.The diagram presenting the relationship between the connectivity probability on one road segment and the average number of vehicles in each tuple was depicted by Rstudio.As a consequence，the model of connectivity probability on one path was achieved by calculating the products of the connectivity probability on all road segments along one path.The analysis result shows that the connectivity probability on one path can be improved by increasing the communication range or the density of vehicles.